Accurate and sensitive probing of onset of micellization based on absolute aggregation‐caused quenching effect. Issue 5 (20th January 2022) - He, Haisheng; Liu, Chang; Ming, Jiang; Lv, Yongjiu; Qi, Jianping; Lu, Yi; Dong, Xiaochun; Zhao, Weili; Wu, Wei
Abstract: Probing the onset of micellization, or determining the critical micelle concentration (CMC), is of crucial importance while remains to be challenged by growing demand for extraordinary sensitivity and accuracy. Although fluorometry has attracted wide attention owing to its superiority in simplicity and sensitivity over other methods, the presence and fluctuation of background fluorescence of conventional fluorescent probes undermine the accuracy of CMC determination. Herein, a series of novel fluorescent probes without background fluorescence at a concentration below CMC owing to absolute aggregation‐caused quenching (aACQ) are utilized for sensitive and accurate measurement of CMC. The aACQ probes aggregate spontaneously and instantly in an aqueous environment owing to molecular π–π stacking with fluorescence quenching absolutely. Therefore, the absence of background fluorescence at a concentration below CMC clears relevant interference associated with conventional fluorophores. In this study, the new method is applied for versatile surfactants with CMCs ranging from nanomolar to millimolar concentrations, especially copolymers with ultralow CMC. The higher sensitivity and accuracy are highlighted by comparison with conventional probes. Abstract : A novel method based on absolute aggregation‐caused quenching (aACQ) probes is reported for critical micelle concentration (CMC) determination. These probes show absolutely no emission before micellization owing to molecular π–π stacking, while abruptly emit high and stable fluorescence upon micellization. Fast fluorescence "off/on" switching upon micellization/demicellization and background‐free property make them outperform common probes for accurate and sensitive determination of ultralow CMCs.